Nitrogen-doped carbon nanotube / copper composite fiber and preparation method and application thereof

By nitrogen doping the surface of the carbon nanotube fiber and copper plating on the surface, nitrogen-doped carbon nanotube/copper composite fiber is obtained, which solves the problems of insufficient adhesion and uneven deposition of copper layers in the prior art, and achieves a high-performance composite fiber material.

CN119736788AActive Publication Date: 2025-04-01SUZHOU INST OF NANO TECH & NANO BIONICS CHINESE ACEDEMY OF SCI
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411758293.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-04-01
Estimated Expiration
2044-12-02

AI Technical Summary

Technical Problem

The existing carbon nanotube/copper composite fibers have weak adhesion between the copper layer and the carbon nanotube fibers, and the copper layer is unevenly deposited, which affects the conductive and mechanical properties of the material. At the same time, the copper plating process is complex and the operating conditions are strict.

Method used

By nitrogen doping the surface of the carbon nanotube fiber, the hydrophilicity of the interface is improved, and copper plating is performed on the surface of the nitrogen-doped carbon nanotube fiber to obtain nitrogen-doped carbon nanotube/copper composite fiber.

Benefits of technology

The bonding strength of the copper/carbon nanotube interface is improved, the uniform deposition of the copper layer is promoted, the conductivity and tensile strength of the material are enhanced, the process flow is simplified, and the cost is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119736788A_ABST
    Figure CN119736788A_ABST
Patent Text Reader

Abstract

The invention discloses a nitrogen-doped carbon nanotube / copper composite fiber and a preparation method and application thereof. The nitrogen-doped carbon nanotube / copper composite fiber comprises a nitrogen-doped carbon nanotube fiber and a copper layer coated on the surface of the nitrogen-doped carbon nanotube fiber. The preparation method comprises the following steps: carrying out first annealing treatment on carbon nanotube fibers to obtain treated carbon nanotube fibers; applying a solution containing a nitrogen source to the surface of the treated carbon nanotube fiber, and then carrying out second annealing treatment to obtain a nitrogen-doped carbon nanotube fiber; and carrying out copper plating treatment on the surface of the nitrogen-doped carbon nanotube fiber to prepare the nitrogen-doped carbon nanotube / copper composite fiber. According to the preparation method provided by the invention, the strength of the copper / carbon nanotube composite interface can be effectively improved through nitrogen doping, so that the mechanical property and the conductivity of the carbon nanotube / copper composite fiber are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of composite fibers, and in particular relates to a nitrogen-doped carbon nanotube / copper composite fiber and a preparation method thereof. Background Art

[0002] With the rapid development of electronic technology and electrical equipment, traditional conductive materials such as copper have exposed some limitations in certain demanding applications. The high density of copper limits its use in applications that require lightweight materials, such as aerospace, electric vehicles, and drones. Copper has low mechanical strength and wear resistance and is susceptible to mechanical damage and deformation, which affects its application in high-intensity environments. Although copper has a certain degree of corrosion resistance, its performance is still unsatisfactory in some harsh environments (such as oceans, chemical plants, etc.).

[0003] Carbon nanotubes have extremely high strength and toughness, and are one of the strongest materials known to date. The density of carbon nanotubes is much lower than that of copper, making them an ideal choice for lightweight materials. Carbon nanotubes have extremely high electrical conductivity and can effectively conduct electric current. Carbon nanotubes show excellent stability and corrosion resistance in harsh chemical environments. Carbon nanotube fiber (CNTF) is a macroscopic assembly of carbon nanotubes, which inherits the excellent properties of carbon nanotubes and has the characteristics of high strength, light weight and good conductivity.

[0004] Therefore, researchers have developed a new type of composite material - a carbon nanotube / copper composite fiber, which combines the conductive advantages of copper with the lightweight and high-strength characteristics of carbon nanotubes. For example, CN 116377712A can further improve the conductive properties of the material by plating copper on carbon nanotube fibers, making up for the shortcomings of carbon nanotubes in large-scale current transmission. For example, the copper-plated carbon nanotube fibers of CN112760974A combine the advantages of copper and carbon nanotubes, have high strength and high toughness, and can withstand greater mechanical stress. In the field of microelectronics and flexible electronics, such as CN 117747311A, this material is used to manufacture a high-conductivity, high-capacitance electrode to improve the performance and life of the equipment. Carbon nanotube fiber copper-plated materials can also be used to manufacture lightweight and high-strength wires and structural components, reduce the weight of aircraft and spacecraft, and improve fuel efficiency. Using this composite material in electric vehicles can reduce vehicle weight, improve battery efficiency, and extend driving range.

[0005] However, the existing carbon nanotube / copper composite fibers have the following shortcomings: the adhesion between the carbon nanotube fibers and the copper layer is weak, and the copper-carbon composite interface is not tightly bonded, which easily causes the copper layer to fall off or peel off, affecting the overall performance and service life of the material; and due to the complex microstructure of the carbon nanotube fiber surface, the thickness and uniformity of the copper layer are difficult to control, and local thickness unevenness may occur, affecting the conductivity and mechanical properties; and the copper plating process is complicated, involving multiple steps, and has strict requirements on operating conditions, and the slightest carelessness may lead to plating quality problems. Summary of the invention

[0006] The main purpose of the present invention is to provide a nitrogen-doped carbon nanotube / copper composite fiber and a preparation method and application thereof, so as to overcome the deficiencies in the prior art.

[0007] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention includes:

[0008] One aspect of the present invention provides a nitrogen-doped carbon nanotube / copper composite fiber, which includes a nitrogen-doped carbon nanotube fiber and a copper layer coated on the surface of the nitrogen-doped carbon nanotube fiber.

[0009] Another aspect of the present invention provides a method for preparing nitrogen-doped carbon nanotube / copper composite fibers, comprising:

[0010] Performing a first annealing treatment on the carbon nanotube fibers to obtain treated carbon nanotube fibers;

[0011] applying a solution containing a nitrogen source to the surface of the treated carbon nanotube fiber, and then performing a second annealing treatment to obtain nitrogen-doped carbon nanotube fiber;

[0012] Copper plating is performed on the surface of the nitrogen-doped carbon nanotube fiber to obtain the nitrogen-doped carbon nanotube / copper composite fiber.

[0013] Another aspect of the present invention also provides a nitrogen-doped carbon nanotube / copper composite fiber prepared by the above-mentioned preparation method, wherein the conductivity of the nitrogen-doped carbon nanotube / copper composite fiber is 0.9×10 7 -1.5×10 7 S / m, specific conductivity is 4000-5000S·m 2 / kg.

[0014] Another aspect of the present invention also provides the use of the aforementioned nitrogen-doped carbon nanotube / copper composite fiber in the preparation of a flexible composite conductor.

[0015] Compared with the prior art, the technical solution of the present invention has at least the following advantages:

[0016] The preparation method provided by the present invention performs nitrogen doping on the surface of carbon nanotube fibers. On the one hand, the Cu / C composite interface is more tightly combined than the original carbon nanotube / copper composite fiber. On the other hand, it is beneficial to improve the uniformity of copper layer deposition during the copper plating process to obtain a high-quality copper layer. The nitrogen-doped carbon nanotube / copper composite fiber provided by the present invention has high electrical conductivity and tensile strength, excellent performance, and can be used to prepare flexible composite wires; and the preparation method provided by the present invention is simple and highly controllable, which is beneficial to reducing costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0018] Figure 1 This is a schematic diagram of the preparation process of nitrogen-doped carbon nanotube fibers in a typical embodiment of the present invention;

[0019] Figure 2 A schematic diagram of an electroplating mold and a direct current copper plating device used in a typical embodiment of the present invention;

[0020] Figure 3 This is a scanning electron microscope image of the cross section of the original carbon nanotube / copper composite fiber prepared in Comparative Example 1 of the present invention;

[0021] Figure 4 This is a scanning electron microscope image of a cross section of the nitrogen-doped carbon nanotube / copper composite fiber prepared in Example 1 of the present invention;

[0022] Figure 5 This is a scanning electron microscope image of the surface of the original carbon nanotube / copper composite fiber prepared in Comparative Example 1 of the present invention;

[0023] Figure 6 This is a scanning electron microscope image of the surface of the nitrogen-doped carbon nanotube / copper composite fiber prepared in Example 1 of the present invention;

[0024] Figure 7 This is a comparison chart of the specific conductivity of the original carbon nanotube / copper composite fiber prepared in Comparative Example 1, the high-temperature annealed carbon nanotube / copper composite fiber prepared in Comparative Example 2, and the nitrogen-doped carbon nanotube / copper composite fiber prepared in Example 1;

[0025] Figure 8 This is a scanning electron microscope image of the surface of the nitrogen-doped carbon nanotube / copper composite fiber prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0026] The present invention will be more fully understood by reading the following specific embodiments. However, it should be understood that the specific embodiments disclosed below are only exemplary of the present invention, and the present invention can be embodied in various forms. Therefore, the specific functional details disclosed herein should not be interpreted as limiting, but only as the basis for the claims and as a representative basis for teaching those skilled in the art to adopt the present invention in different ways in any appropriate detailed embodiment.

[0027] As one aspect of the technical solution of the present invention, a nitrogen-doped carbon nanotube / copper composite fiber includes a nitrogen-doped carbon nanotube fiber and a copper layer coated on the surface of the nitrogen-doped carbon nanotube fiber.

[0028] In some embodiments, the copper layer has a thickness of 1-5 μm.

[0029] As another aspect of the technical solution of the present invention, a method for preparing a nitrogen-doped carbon nanotube / copper composite fiber includes:

[0030] Performing a first annealing treatment on the carbon nanotube fibers to obtain treated carbon nanotube fibers;

[0031] applying a solution containing a nitrogen source to the surface of the treated carbon nanotube fiber, and then performing a second annealing treatment to obtain nitrogen-doped carbon nanotube fiber;

[0032] Copper plating is performed on the surface of the nitrogen-doped carbon nanotube fiber to obtain the nitrogen-doped carbon nanotube / copper composite fiber.

[0033] In some embodiments, the carbon nanotubes contained in the carbon nanotube fibers include single-walled carbon nanotubes and / or multi-walled carbon nanotubes.

[0034] In some embodiments, the carbon nanotube fibers include, but are not limited to, carbon nanotube fibers prepared by a floating catalytic method or carbon nanotube fibers prepared by an electrospinning method.

[0035] In some embodiments, the carbon nanotube fibers have a diameter of 30-100 μm.

[0036] In some embodiments, the preparation method includes: performing the first annealing treatment on the carbon nanotube fiber under a protective atmosphere.

[0037] In some preferred embodiments, the protective atmosphere includes, but is not limited to, a nitrogen atmosphere or an argon atmosphere.

[0038] In some preferred embodiments, the temperature of the first annealing treatment is 500-800° C., and the time is 1-3 hours.

[0039] In some embodiments, the concentration of the nitrogen source in the solution containing the nitrogen source is 3-10 mg / mL.

[0040] In some embodiments, the nitrogen source includes, but is not limited to, any one of melamine, polyaniline, pyridine, and urea, or a combination of two or more thereof.

[0041] The present invention uses nitrogen-containing macromolecules such as melamine as a nitrogen source, and achieves modification of nitrogen-containing macromolecules on the surface of carbon nanotube fibers through high-temperature annealing treatment, and then further copper-plating to obtain nitrogen-doped carbon nanotube / copper composite fibers. Nitrogen doping on the surface of carbon nanotube fibers can effectively improve the interfacial hydrophilicity of carbon nanotube fibers, which is beneficial to improving the wettability of copper ions, promoting the uniform deposition of copper on the surface of carbon nanotube fibers and inside some pores of carbon nanotube fibers, and increasing the copper / carbon nanotube interface bonding strength, thereby improving the mechanical properties and conductive properties of carbon nanotube / copper composite fibers.

[0042] In some embodiments, the manner of applying includes but is not limited to soaking.

[0043] In some preferred embodiments, the soaking time is 10-60 minutes.

[0044] In some embodiments, the preparation method includes: performing the second annealing treatment under a protective atmosphere.

[0045] In some preferred embodiments, the protective atmosphere includes but is not limited to any one of nitrogen, argon, and ammonia, or a combination of two or more thereof.

[0046] In some preferred embodiments, the temperature of the second annealing treatment is 500-800° C., and the time is 1-3 hours.

[0047] In some embodiments, the copper plating process is performed by methods including but not limited to electrodeposition.

[0048] In some preferred embodiments, the copper plating process is direct current copper plating, which specifically includes: providing a copper sulfate electrodeposition solution, using a direct current power supply as an external power supply, adopting a dual-electrode system for copper plating, using the nitrogen-doped carbon nanotube fiber as the negative electrode, and using a copper plate as the positive electrode.

[0049] In some more preferred embodiments, the copper sulfate electrodeposition solution is obtained by mixing copper sulfate, concentrated sulfuric acid, concentrated hydrochloric acid and water in a mass volume ratio of (100-300) g: (10-500) mL: (100-1000) μL: (1-3) L.

[0050] In some more preferred embodiments, the current of the DC power supply is 5-10 mA.

[0051] In some more preferred embodiments, the copper plating treatment time is 10-60s.

[0052] In some specific embodiments, the method for preparing the nitrogen-doped carbon nanotube / copper composite fiber comprises the following steps:

[0053] (1) annealing the carbon nanotube fibers at a high temperature (500-800° C., treatment time 1-3 h) in an inert gas (e.g., nitrogen or argon) atmosphere;

[0054] (2) Then, the high-temperature annealed carbon nanotube fibers are immersed in a nitrogen-containing solution, dried (80° C., 2-10 h), and subjected to a secondary high-temperature annealing process to obtain nitrogen-doped carbon nanotube fibers; the nitrogen-containing solution is mainly a nitrogen-containing macromolecular solution, including melamine, polyaniline, pyridine, urea, etc.; the concentration of the nitrogen-containing macromolecular solution is controlled at 3-10 mg / mL, and the immersion time is 10-60 min;

[0055] (3) 180 g of CuSO4·5H2O, 33 mL of concentrated sulfuric acid and 100 μL of concentrated hydrochloric acid are dissolved in 1 L of deionized water to prepare a copper sulfate electrodeposition solution, and a nitrogen-doped carbon nanotube / copper composite fiber is prepared by an electrodeposition method (e.g., direct current copper plating). The direct current copper plating method specifically comprises the following steps: using a direct current power supply as an external power supply, using a double-electrode system for copper plating, using nitrogen-doped carbon nanotube fibers as a negative electrode, and two symmetrically placed copper plates as a positive electrode for direct current copper plating.

[0056] The nitrogen doping in the nitrogen-doped carbon nanotube fiber described in the present invention can effectively promote the uniform deposition of copper on the surface of the carbon nanotube fiber and inside some pores, enhance the interface composite of copper / carbon nanotube, and form a core-shell structured nitrogen-doped carbon nanotube / copper composite fiber.

[0057] In some specific embodiments, the preparation process of the nitrogen-doped carbon nanotube fibers is as follows: Figure 1 As shown, the carbon nanotube fiber (CNTF) is first subjected to high-temperature annealing in an argon atmosphere at 500°C, and then the high-temperature annealed carbon nanotube fiber (tCNTF) is immersed in a nitrogen-containing solution (such as a melamine solution) to obtain the immersed carbon nanotube (tCNTF@N), which is then dried and subjected to high-temperature annealing again to obtain nitrogen-doped carbon nanotube fiber (CNTF@N).

[0058] In some more specific implementation schemes, the Figure 2 The electroplating mold and direct current copper plating device shown perform copper plating treatment on the surface of the nitrogen-doped carbon nanotube fiber (CNTF@N) by electrodeposition to obtain nitrogen-doped carbon nanotube / copper composite fiber.

[0059] As another aspect of the technical solution of the present invention, it also relates to the nitrogen-doped carbon nanotube / copper composite fiber prepared by the above-mentioned preparation method, wherein the conductivity of the nitrogen-doped carbon nanotube / copper composite fiber is 0.9×10 7 -1.5×10 7 S / m, specific conductivity is 4000-5000S·m 2 / kg.

[0060] As another aspect of the technical solution of the present invention, it also involves the use of the aforementioned nitrogen-doped carbon nanotube / copper composite fiber in the preparation of a flexible composite conductor.

[0061] In summary, the present invention firstly performs high temperature annealing on carbon nanotube fibers, then immerses the high temperature annealed carbon nanotube fibers in a nitrogen-containing solution, performs secondary high temperature annealing, obtains nitrogen-doped carbon nanotube fibers, and finally uses an electrochemical deposition method to prepare nitrogen-doped carbon nanotube / copper composite fibers. The preparation method of the present invention is simple and controllable, and the nitrogen-doped modified carbon nanotube fibers can effectively improve the copper / carbon nanotube composite interface strength, thereby improving the mechanical properties and electrical conductivity of the carbon nanotube / copper composite fibers, providing a new design idea for future lightweight and flexible composite conductor systems.

[0062] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The reagents and raw materials used in the following examples are commercially available, and the experimental methods without specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturers.

[0063] Example 1

[0064] This embodiment provides a nitrogen-doped carbon nanotube / copper composite fiber, and the preparation method thereof is as follows:

[0065] (1) High-temperature annealing of carbon nanotube fibers prepared by the floating catalytic method in a nitrogen atmosphere. The diameter of the carbon nanotube fibers is 30 μm, the high-temperature annealing temperature is 500°C, and the annealing time is 2 h;

[0066] (2) Prepare a 5 mg / mL melamine solution, dissolve the melamine powder in a mixed solution of ethanol and water, where the volume ratio of ethanol to water is 3:7, and stir at a constant temperature of 60°C until the solution becomes clear and transparent. Soak the carbon nanotube fibers in the melamine solution for 10 minutes, dry (dry at 80°C for 3 hours), and perform secondary high-temperature annealing to prepare nitrogen-doped carbon nanotube fibers. The secondary high-temperature annealing temperature is 500°C for 2 hours, and the annealing atmosphere is nitrogen;

[0067] (3) 180 g of CuSO4·5H2O, 33 mL of concentrated sulfuric acid and 100 μL of concentrated hydrochloric acid were dissolved in 1 L of deionized water to prepare a copper sulfate electrodeposition solution. A DC power supply was used as an external power supply and a two-electrode system was used for copper plating, wherein the nitrogen-doped carbon nanotube fiber was used as the negative electrode and the symmetrically placed copper plate was used as the positive electrode. The copper plating current was set to 5 mA and the copper plating time was set to 20 s.

[0068] (4) After copper plating, the nitrogen-doped carbon nanotube / copper composite fiber is repeatedly washed with deionized water to remove residual electrolyte. Finally, the composite fiber is naturally dried at room temperature to obtain the final nitrogen-doped carbon nanotube / copper composite fiber. The surface scanning electron micrograph of the composite fiber is shown in FIG. Figure 8 .

[0069] The conductivity of the prepared nitrogen-doped carbon nanotube / copper composite fiber is 1.02×10 7 S / m, specific conductivity is 4196S·m 2 / kg.

[0070] Example 2

[0071] This embodiment provides a nitrogen-doped carbon nanotube / copper composite fiber, and the preparation method thereof is as follows:

[0072] (1) High-temperature annealing of carbon nanotube fibers prepared by the floating catalytic method in a nitrogen atmosphere. The diameter of the carbon nanotube fibers is 30 μm, the high-temperature annealing temperature is 500°C, and the annealing time is 2 h;

[0073] (2) Prepare a 5 mg / mL melamine solution, dissolve the melamine powder in a mixed solution of ethanol and water, where the volume ratio of ethanol to water is 3:7, and stir at a constant temperature of 60°C until the solution becomes clear and transparent. Soak the carbon nanotube fibers in the melamine solution for 20 minutes, dry (dry at 80°C for 3 hours), and perform secondary high-temperature annealing to prepare nitrogen-doped carbon nanotube fibers. The secondary high-temperature annealing temperature is 500°C for 2 hours, and the annealing atmosphere is nitrogen;

[0074] (3) 180 g of CuSO4·5H2O, 33 mL of concentrated sulfuric acid and 100 μL of concentrated hydrochloric acid were dissolved in 1 L of deionized water to prepare a copper sulfate electrodeposition solution. A DC power supply was used as an external power supply and a double-electrode system was used for copper plating, in which the nitrogen-doped carbon nanotube fiber was used as the negative electrode and the symmetrically placed copper plate was used as the positive electrode. The copper plating current was set to 5 mA and the copper plating time was set to 40 s.

[0075] (4) After the copper plating is completed, the nitrogen-doped carbon nanotube / copper composite fiber is repeatedly washed with deionized water to remove the residual electrolyte. Finally, the composite fiber is naturally dried at room temperature to obtain the final nitrogen-doped carbon nanotube / copper composite fiber.

[0076] The conductivity of the prepared nitrogen-doped carbon nanotube / copper composite fiber is 1.11×10 7 S / m, specific conductivity is 4387S·m 2 / kg.

[0077] Example 3

[0078] This embodiment provides a nitrogen-doped carbon nanotube / copper composite fiber, and the preparation method thereof is as follows:

[0079] (1) High-temperature annealing of carbon nanotube fibers prepared by the floating catalytic method in a nitrogen atmosphere. The diameter of the carbon nanotube fibers is 30 μm, the high-temperature annealing temperature is 500°C, and the annealing time is 2 h;

[0080] (2) Prepare a 5 mg / mL melamine solution, dissolve the melamine powder in a mixed solution of ethanol and water, wherein the volume ratio of ethanol to water is 3:7, and stir at a constant temperature of 60°C until the solution becomes clear and transparent. Soak the carbon nanotube fibers in the melamine solution for 60 minutes, dry (dry at 80°C for 3 hours), and perform secondary high-temperature annealing to prepare nitrogen-doped carbon nanotube fibers. The secondary high-temperature annealing temperature is 600°C for 2 hours, and the annealing atmosphere is nitrogen;

[0081] (3) 180 g of CuSO4·5H2O, 33 mL of concentrated sulfuric acid and 100 μL of concentrated hydrochloric acid were dissolved in 1 L of deionized water to prepare a copper sulfate electrodeposition solution. A DC power supply was used as an external power supply and a two-electrode system was used for copper plating, wherein the nitrogen-doped carbon nanotube fiber was used as the negative electrode and the symmetrically placed copper plate was used as the positive electrode. The copper plating current was set to 5 mA and the copper plating time was set to 60 s.

[0082] (4) After the copper plating is completed, the nitrogen-doped carbon nanotube / copper composite fiber is repeatedly washed with deionized water to remove the residual electrolyte. Finally, the composite fiber is naturally dried at room temperature to obtain the final nitrogen-doped carbon nanotube / copper composite fiber.

[0083] The conductivity of the prepared nitrogen-doped carbon nanotube / copper composite fiber is 1.42×10 7 S / m, specific conductivity is 4807S·m 2 / kg.

[0084] Example 4

[0085] This embodiment provides a nitrogen-doped carbon nanotube / copper composite fiber, and the preparation method thereof is as follows:

[0086] (1) High-temperature annealing of carbon nanotube fibers prepared by the floating catalytic method in a nitrogen atmosphere. The diameter of the carbon nanotube fibers is 50 μm, the high-temperature annealing temperature is 650°C, and the annealing time is 3 h;

[0087] (2) Prepare a 3 mg / mL melamine solution, dissolve the melamine powder in a mixed solution of ethanol and water, where the volume ratio of ethanol to water is 3:7, and stir at a constant temperature of 60°C until the solution becomes clear and transparent. Soak the carbon nanotube fibers in the melamine solution for 20 minutes, dry (dry at 80°C for 2 hours), and perform secondary high-temperature annealing to prepare nitrogen-doped carbon nanotube fibers. The secondary high-temperature annealing temperature is 500°C for 3 hours, and the annealing atmosphere is nitrogen;

[0088] (3) 100 g of CuSO4·5H2O, 10 mL of concentrated sulfuric acid and 500 μL of concentrated hydrochloric acid were dissolved in 2 L of deionized water to prepare a copper sulfate electrodeposition solution. A DC power supply was used as an external power supply and a double-electrode system was used for copper plating, in which the nitrogen-doped carbon nanotube fiber was used as the negative electrode and the symmetrically placed copper plate was used as the positive electrode. The copper plating current was set to 8 mA and the copper plating time was set to 10 s.

[0089] (4) After the copper plating is completed, the nitrogen-doped carbon nanotube / copper composite fiber is repeatedly washed with deionized water to remove the residual electrolyte. Finally, the composite fiber is naturally dried at room temperature to obtain the final nitrogen-doped carbon nanotube / copper composite fiber.

[0090] Example 5

[0091] This embodiment provides a nitrogen-doped carbon nanotube / copper composite fiber, and the preparation method thereof is as follows:

[0092] (1) High-temperature annealing of carbon nanotube fibers prepared by the floating catalytic method in a nitrogen atmosphere. The diameter of the carbon nanotube fibers is 100 μm, the high-temperature annealing temperature is 800°C, and the annealing time is 1 h;

[0093] (2) Prepare a 10 mg / mL melamine solution, dissolve melamine powder in a mixed solution of ethanol and water, wherein the volume ratio of ethanol to water is 3:7, and stir at a constant temperature of 60°C until the solution becomes clear and transparent. Soak the carbon nanotube fibers in the melamine solution for 20 minutes, dry (dry at 80°C for 10 hours), and perform secondary high-temperature annealing to prepare nitrogen-doped carbon nanotube fibers. The secondary high-temperature annealing temperature is 800°C for 1 hour, and the annealing atmosphere is nitrogen;

[0094] (3) 300 g of CuSO4·5H2O, 500 mL of concentrated sulfuric acid and 1000 μL of concentrated hydrochloric acid were dissolved in 3 L of deionized water to prepare a copper sulfate electrodeposition solution. A DC power supply was used as an external power supply and a double-electrode system was used for copper plating, in which the nitrogen-doped carbon nanotube fiber was used as the negative electrode and the symmetrically placed copper plate was used as the positive electrode. The copper plating current was set to 10 mA and the copper plating time was set to 60 s.

[0095] (4) After the copper plating is completed, the nitrogen-doped carbon nanotube / copper composite fiber is repeatedly washed with deionized water to remove the residual electrolyte. Finally, the composite fiber is naturally dried at room temperature to obtain the final nitrogen-doped carbon nanotube / copper composite fiber.

[0096] Comparative Example 1

[0097] (1) The carbon nanotube fibers prepared by the floating catalytic method are not annealed. The diameter of the carbon nanotube fibers is 30 μm;

[0098] (2) 180 g of CuSO4·5H2O, 33 mL of concentrated sulfuric acid and 100 μL of concentrated hydrochloric acid were dissolved in 1 L of deionized water to prepare a copper sulfate electrodeposition solution. A DC power supply was used as an external power supply and a double-electrode system was used for copper plating. Undoped carbon nanotube fibers were used as the negative electrode and a symmetrically placed copper plate was used as the positive electrode. The copper plating current was set to 5 mA and the copper plating time was set to 20 s.

[0099] (3) After the copper plating is completed, the carbon nanotube / copper composite fiber is repeatedly washed with deionized water to remove the residual electrolyte. Finally, the composite fiber is naturally dried at room temperature to obtain the original carbon nanotube / copper composite fiber.

[0100] The conductivity of the prepared carbon nanotube / copper composite fiber is 6.94×10 6 S / m, specific conductivity is 3004S·m 2 / kg.

[0101] Comparative Example 2

[0102] (1) High-temperature annealing of carbon nanotube fibers prepared by the floating catalytic method in a nitrogen atmosphere. The diameter of the carbon nanotube fibers is 30 μm, the high-temperature annealing temperature is 500°C, and the annealing time is 1 h;

[0103] (2) 180 g of CuSO4·5H2O, 33 mL of concentrated sulfuric acid and 100 μL of concentrated hydrochloric acid were dissolved in 1 L of deionized water to prepare a copper sulfate electrodeposition solution. A DC power supply was used as an external power supply and a double-electrode system was used for copper plating. Undoped carbon nanotube fibers were used as the negative electrode and a symmetrically placed copper plate was used as the positive electrode. The copper plating current was set to 5 mA and the copper plating time was set to 20 s.

[0104] (3) After the copper plating is completed, the carbon nanotube / copper composite fiber is repeatedly washed with deionized water to remove the residual electrolyte. Finally, the composite fiber is naturally dried at room temperature to obtain a high temperature annealed carbon nanotube / copper composite fiber.

[0105] The electrical conductivity of the prepared carbon nanotube / copper composite fiber is 8.93×10 6 S / m, specific conductivity is 3968S·m 2 / kg.

[0106] like Figure 3 , Figure 4 , Figure 5 and Figure 6 As shown in the figure, by comparing the scanning electron microscope images of the cross section and surface of the original carbon nanotube / copper composite fiber and the scanning electron microscope images of the cross section and surface of the nitrogen-doped carbon nanotube / copper composite fiber, it can be seen that the copper-carbon interface is more tightly bonded after nitrogen doping, the copper layer is more uniform, and the copper layer surface is smoother; Figure 7 As shown, compared with the original carbon nanotube / copper composite fiber (CNTF) and high temperature annealed carbon nanotube / copper composite fiber (CNTF-500℃), the specific conductivity of nitrogen-doped carbon nanotube / copper composite fiber (CNTF@N) is significantly improved.

[0107] In addition, the inventors of this case also referred to the aforementioned embodiments and conducted experiments with other raw materials, process operations, and process conditions described in this specification, and obtained relatively ideal results.

[0108] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A nitrogen-doped carbon nanotube / copper composite fiber, characterized in that: The nitrogen-doped carbon nanotube / copper composite fiber comprises a nitrogen-doped carbon nanotube fiber and a copper layer coated on the surface of the nitrogen-doped carbon nanotube fiber.

2. The nitrogen-doped carbon nanotube / copper composite fiber according to claim 1, characterized in that: The copper layer has a thickness of 1-5 μm.

3. A method for preparing nitrogen-doped carbon nanotube / copper composite fibers, characterized in that: include: Performing a first annealing treatment on the carbon nanotube fibers to obtain treated carbon nanotube fibers; applying a solution containing a nitrogen source to the surface of the treated carbon nanotube fiber, and then performing a second annealing treatment to obtain nitrogen-doped carbon nanotube fiber; The surface of the nitrogen-doped carbon nanotube fiber is subjected to copper plating treatment to obtain the nitrogen-doped carbon nanotube / copper composite fiber.

4. The preparation method according to claim 3, characterized in that: The carbon nanotubes contained in the carbon nanotube fibers include single-walled carbon nanotubes and / or multi-walled carbon nanotubes; And / or, the carbon nanotube fibers include carbon nanotube fibers prepared by a floating catalytic method or carbon nanotube fibers prepared by an electrostatic spinning method; And / or, the diameter of the carbon nanotube fiber is 30-100 μm; And / or, the preparation method comprises: performing the first annealing treatment on the carbon nanotube fibers under a protective atmosphere; Preferably, the protective atmosphere comprises a nitrogen atmosphere or an argon atmosphere; Preferably, the temperature of the first annealing treatment is 500-800° C., and the time is 1-3 hours.

5. The preparation method according to claim 3, characterized in that: The concentration of the nitrogen source in the solution containing the nitrogen source is 3-10 mg / mL; And / or, the nitrogen source includes any one or a combination of two or more of melamine, polyaniline, pyridine and urea; and / or, the applying method comprises soaking; Preferably, the soaking time is 10-60 min.

6. The preparation method according to claim 3, characterized in that: include: Performing the second annealing treatment under a protective atmosphere; Preferably, the protective atmosphere includes any one of nitrogen, argon, and ammonia, or a combination of two or more thereof; Preferably, the temperature of the second annealing treatment is 500-800° C. and the time is 1-3 hours.

7. The preparation method according to claim 3, characterized in that: The copper plating treatment adopts an electrodeposition method; Preferably, the copper plating process is direct current copper plating, which specifically includes: providing a copper sulfate electrodeposition solution, using a direct current power supply as an external power supply, adopting a double electrode system for copper plating, using the nitrogen-doped carbon nanotube fiber as the negative electrode, and using a copper plate as the positive electrode.

8. The preparation method according to claim 7, characterized in that: The copper sulfate electrodeposition solution is obtained by mixing copper sulfate, concentrated sulfuric acid, concentrated hydrochloric acid and water in a mass volume ratio of (100-300) g: (10-500) mL: (100-1000) μL: (1-3) L; And / or, the current of the DC power supply is 5-10mA; And / or, the copper plating treatment time is 10-60s.

9. The nitrogen-doped carbon nanotube / copper composite fiber prepared by the preparation method according to any one of claims 3 to 8, characterized in that: The conductivity of the nitrogen-doped carbon nanotube / copper composite fiber is 0.9×10 7 -1.5×10 7 S / m, specific conductivity is 4000-5000S·m 2 / kg.

10. Use of the nitrogen-doped carbon nanotube / copper composite fiber according to any one of claims 1, 2 and 9 in preparing a flexible composite conductor.

Citation Information

Patent Citations

  • Carbon nanotube-copper composite fiber and preparation method thereof

    CN112760974A

  • Preparation method of carbon nanotube / copper core-shell structure fiber with ultrahigh specific conductivity and ultrahigh current-carrying capacity

    CN116377712A

  • Cuprous sulfide / carbon nanotube fiber electrode and preparation method and application thereof

    CN117747311A

  • Copper-CNT (carbon nano tube) composite fiber material and preparation method thereof

    CN103726305A

  • Preparation method of nitrogen-doped carbon nanotube reinforced high-conductivity copper-based composite material

    CN116727676A